Bibliometric analysis of research trends in college students' mobile phone addiction from 2013 to 2023 - Wang, Ruifeng; Abd Karim, Sairah; Tham, Jacquline (International Journal of Public Health Science (IJPHS), 2025)
Mobile phone addiction (MPA) among college students is a growing concern affecting physical and mental well-being. This study employs CiteSpace 6.2.R6 to analyze research trends on MPA. A total of 957 articles published between 2013 and 2023 were analyzed, with key contributors including Griffiths, Mark D, and institutions like Nottingham Trent University and Toledo University. "Computers In Human Behavior" emerged as the most cited journal. Research focal points include the prevalence of MPA, its health effects, and its association with social media usage. Future research should focus on understanding the MPA-mental health correlation, improving methodologies, and conducting diverse intervention studies. This study identifies research hotspots and emphasizes the need for further investigations to expand understanding of MPA among college students. Collaboration between institutions and authors is crucial, along with diversification of research methods and tools.